Kinetic Study of the Hydrogen Oxidation Reaction on Membrane Coated Electrodes. Part I: Theoretical Aspects - Marozzi, Carlos Alberto (2009)
A generalized theoretical analysis of the kinetics of the hydrogen oxidation reaction under the Volmer-Heyrovsky-Tafel mechanism on an electrode covered by polymeric films is presented. The treatment includes the diffusion of the molecular hydrogen through the electrolyte solution, as well as through the different layers and interfaces. On the light of the resulting expressions, the applicability of the Levich-Koutecky diagrams for the determination of the kinetic current densities was critically analyzed.